A Review of Isolation Gowns in Healthcare: Fabric and Gown Properties. Issue 3 (September 2015) - Kilinc, F. Selcen
The threat of emerging infectious diseases including Ebola hemorrhagic fever, pandemic influenza, avian influenza, Hepatitis B, Hepatitis C, and SARS has highlighted the need for effective personal protective equipment (PPE) to protect healthcare workers (HCWs), patients, and visitors. PPE is a critical component in the hierarchy of controls used to protect HCWs from infectious hazards. HCW PPE may include gowns, respirators, face masks, gloves, eye protection, face shields, and head and shoe coverings. Important research has been conducted in certain areas, such as respirators and protective masks, but studies in other areas, particularly gowns, are scarce. Gowns are identified as the second-most-used piece of PPE, following gloves, in the healthcare setting. According to the Centers for Disease Control and Prevention's Guideline for Isolation Precautions, isolation gowns should be worn to protect HCWs' arms and exposed body areas during procedures and patient-care activities when anticipating contact with clothing, blood, bodily fluids, secretions and excretions. Isolation gowns currently available on the marketplace offer varying resistance to blood and other bodily fluids depending on the type of the material, its impermeability, and wear and tear. While some studies show no benefit of the routine use of isolation gowns, others demonstrate that its use is associated with a reduced infection rate. This paper reviews isolation gowns in healthcare settings, including the fabrics used, gown design and interfaces, as well as critical parameters that affect microorganism and liquid transmission through fabrics.